Interplay between spin proximity effect and charge-dependent exciton dynamics in MoSe2/CrBr3 van der Waals heterostructures - T. P. Lyons (Nature Portfolio, 2020)
One advantage of van der Waals materials is the ability to combine different materials in layers to form new heterostructures. Here, the authors investigate heterostructures of CrBr3 and MoSe2, and find that the ferromagnetism of CrBr3 enhances the valley dependent optical response of the MoSe2.